2021
DOI: 10.3389/fpsyg.2021.620251
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Research on Automatic Voice and Speech Analysis of People With Alzheimer's Disease and Mild Cognitive Impairment: A Systematic Review Article

Abstract: Background: The field of voice and speech analysis has become increasingly popular over the last 10 years, and articles on its use in detecting neurodegenerative diseases have proliferated. Many studies have identified characteristic speech features that can be used to draw an accurate distinction between healthy aging among older people and those with mild cognitive impairment and Alzheimer's disease. Speech analysis has been singled out as a cost-effective and reliable method for detecting the presence of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 62 publications
3
74
0
Order By: Relevance
“…Advances in signal processing and natural language processing have enabled objective analysis of speech samples for both their acoustic properties and linguistic content, providing a window into motor, linguistic and cognitive abilities. Most importantly, previous research has extensively shown that speech patterns are affected in MCI and AD, demonstrating the clinical relevance of speech for detecting cognitive impairment and dementia (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Advances in signal processing and natural language processing have enabled objective analysis of speech samples for both their acoustic properties and linguistic content, providing a window into motor, linguistic and cognitive abilities. Most importantly, previous research has extensively shown that speech patterns are affected in MCI and AD, demonstrating the clinical relevance of speech for detecting cognitive impairment and dementia (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…Much of the previous work studying speech patterns in AD using automated speech analysis has focused on multivariate classification models to differentiate those with AD or MCI from healthy controls based on their speech (9)(10)(11). These models generally achieve high accuracy (80-90%) demonstrating that there are robust differences between clinical groups based on speech characteristics (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Research documents changes in vocal and linguistic speech patterns in AD, primarily in cohorts with more progressed AD and without biomarker confirmation 13,25 . The current findings show detectable changes in speech occurring earlier in the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…Speech responses are a common component of cognitive tests, however data generated in these tests, including those reported in this study, often relate to simple pass/fail characteristics of response accuracy. New metrics using audio-and text-based AI models to target other changes measurable in speech data (acoustic [30,31], semantic [32][33][34][35], linguistic [31]) in early-stage Alzheimer's disease could further leverage the information content of ASRTs, developing a new class of powerful, fully automated speech biomarkers.…”
Section: Overview and Future Directionsmentioning
confidence: 99%